Wild Words: Essays on Alberta Literature - Donna Coates (Athabasca University Press, 2009)
As the first collection of literary criticism focusing on Alberta writers, Wild Words establishes a basis for identifying Alberta fiction, poetry, drama, and nonfiction as valid subjects of study in their own right. By critically situating and assessing specific Alberta authors according to genre, this volume continues the work begun with Melnyk's Literary History of Alberta.